SURVEY AND MOLECULAR DETECTION FOR INFECTIOUS CORYZA OF POULTRY IN IRAQ - Owaid , Sh.J.; Ulaiwi, A. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The current study was aimed at case recording and molecular detection of infectious coryza in chickens. Samples were collected and identified for Avibacterium paragallinarum from about 68 poultry farms for eight months from different five provinces Baghdad, Diyala, Babil, Salahuddin, and Wasit from different flock layers and broilers. Diagnosis of bacterial colonies was first done by isolation and microbiological and biochemical tests. From 15 nasal samples of respiratory sinus cases of chicken,6 isolates were A. paragallinarum, additionally, PCR technique was used to confirm A. paragallinarum, the results for these bacteria in this study were detected in 6 isolates from 15 samples of poultry, Then, after, the result of sequences of A. paragallinarum serogroup C Sequence ID: KJ867498.This study concluded that A. paragallinarum is known to be a significant pathogen causing respiratory infection and economic losses.